Vav Proteins in Neutrophils Are Required for FcγR-Mediated Signaling to Rac GTPases and Nicotinamide Adenine Dinucleotide Phosphate Oxidase Component p40(phox) - Ahmad Utomo; Xavier Culleré; Michael Glogauer; Wojciech Swat; Tanya N. Mayadas (2006)
Phagocytes generate reactive oxygen species, the regulation of which is important in eliminating ingested microbes while limiting tissue damage. Clustering of FcgammaRs results in the activation of Vav proteins, Rho/Rac guanine nucleotide exchange factors, and results in robust superoxide generation through the NADPH oxidase. In this study, studies in neutrophils isolated from mice deficient in Vav or Rac isoforms demonstrate a critical role for Vav3 in Rac2-dependent activation of the NADPH oxidase following FcgammaR clustering. However, studies in cytokine-primed cells revealed a strict requirement for Vav1 and Vav3 and Rac1 and Rac2 in the FcgammaR-mediated oxidative burst. In comparison, Vav was not essential for PMA or G protein-coupled receptor-mediated superoxide generation. The FcgammaR-mediated oxidative burst defect in Vav-deficient cells was linked to aberrant Rac activation as well as Rac- and actin-polymerization-independent, but PI3K-dependent, phosphorylation of the NADPH oxidase component p40(phox). In macrophages, Vav regulation of Rac GTPases was required specifically in FcgammaR-mediated activation of the oxidative burst, but not in phagocytosis. Thus, Vav proteins specifically couple FcgammaR signaling to NADPH oxidase function through a Rac-dependent as well as an unexpected Rac-independent signal that is proximal to NADPH oxidase activation and does not require actin polymerization.